2015
DOI: 10.1186/s13058-015-0569-0
|View full text |Cite
|
Sign up to set email alerts
|

Adipose cells promote resistance of breast cancer cells to trastuzumab-mediated antibody-dependent cellular cytotoxicity

Abstract: IntroductionTrastuzumab has been used in the treatment of human epidermal growth factor receptor 2 (HER2)-expressing breast cancer, but its efficacy is limited by de novo or acquired resistance. Although many mechanisms have been proposed to explain resistance to trastuzumab, little is known concerning the role of the tumor microenvironment. Given the importance of antibody-dependent cellular cytotoxicity (ADCC) in the antitumor effect of trastuzumab and the abundance of adipose tissue in the breast, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 46 publications
2
85
0
2
Order By: Relevance
“…SV40TAg mice on the HAFD did not gain significantly more weight compared with the mice on a regular diet, suggesting that critical changes affecting tumor growth occur in the mammary glands independently of systemic obesity . It has been also suggested that an inflammatory state exists in animal models that is associated with excess systemic adiposity resulting from high fat diet consumption, which then promotes mammary cancer progression . The connection between high fat diet/obesity and breast cancer has been attributed in part to adipose tissue dysfunction, which may occur locally within mammary fat pads, even in the absence of systemic increased adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…SV40TAg mice on the HAFD did not gain significantly more weight compared with the mice on a regular diet, suggesting that critical changes affecting tumor growth occur in the mammary glands independently of systemic obesity . It has been also suggested that an inflammatory state exists in animal models that is associated with excess systemic adiposity resulting from high fat diet consumption, which then promotes mammary cancer progression . The connection between high fat diet/obesity and breast cancer has been attributed in part to adipose tissue dysfunction, which may occur locally within mammary fat pads, even in the absence of systemic increased adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced antitumor effect was observed in mice which had tumors in close proximity to a lipoma, while in another group of mice which had tumors located distant to the lipoma, the trastuzumab anti-tumor effects were enhanced. The inhibition of antitumor activity was enhanced when the adipocytes were in hypoxic conditions, these factors might suggest a link between patient obesity and development of trastuzumab resistance mechanisms[76]. …”
Section: Targeted Therapies In Breast Cancermentioning
confidence: 99%
“…Adipocytes cross-talk with tumor cells to promote growth and metastases, and further enhance chemotherapeutic resistance by impairing mechanisms of tumor cell killing and sequestering drugs. For example, trastuzumab is a critical antibody-based chemotherapeutic against breast cancer which mediates tumor cell killing by natural killer cells and ADCC mechanisms, and adipocytes suppress such tumor cell killing by secreting factors that impair NK cell functions [102]. Additionally, daunorubicin is another important chemotherapeutic for leukemias and adipocytes enhance survival of acute lymphoblastic leukemia cells by secreting factors which protect the tumor cells from oxidative stress, as well as by accumulating and inactivating significant amounts of daunorubicin [103, 104].…”
Section: Antiretroviral Therapy and Adipose Tissuementioning
confidence: 99%